Bien fait? Mal fait? Pas fait? - Mühleis, Volkmar (Gent Sint-Lucas, 2007)
Bien fait? Mal Fait? Pas fait? Regarding the artistic practice is an audiovisual book that invites you to reflect, enjoy, ansd think further on the questions, irritations and stimulations of the artistic labour. It documents via photo, essays, videos and audio material an event that took place in October 2007 at Sint-Lucas visual arts Ghent: the symposium Bien fait? Mal Fait? Pas fait? As well as the exhibtion Multispeak. During twop days, artists, scientists, philosophers, students and others were discussing their thoughts and ideas on terms as artistic research, the roles of the artist, possible worlds, the myths of creativity and orginiality, the complementarities of practice and theory, etc. It was a highly heterogeneous programme, with many productive option in the end instead of an answer. In this sense, the book offers you the humus of our debate, impressions of the exhibition and quotations from the artists themselves, to initiate hopefully further entanglements of theory and practice in the Arts. With contributions by Michaela Meliàn, Angelo Vermeulen, Ridu Laermans, Sabien Kampmann, Ernst van de Wetering, Géry d'Ydewalle, Paul Cruysberghs, Herman Parret and Philippe Junod.